Reliability of a clinical 3D freehand ultrasound technique: Analyses on healthy and pathological muscles. (March 2018) - Cenni, Francesco; Schless, Simon-Henri; Bar-On, Lynn; Aertbeliën, Erwin; Bruyninckx, Herman; Hanssen, Britta; Desloovere, Kaat
Highlights: Simplified approach for extracting relevant clinical outcomes is proposed and evaluated. Effectiveness of 3DfUS as a clinical tool for differentiating between healthy and pathological medial gastrocnemius muscles. The inherent levels of error provide a useful reference for the wider community using this 3DfUS technique. Details of the current software implementation are available in an open-source software library. Abstract: Background and objective: 3D freehand Ultrasonography is a medical imaging technique that can be used to measure muscle and tendon morphological and structural properties, including volume, lengths and echo-intensity. These properties are clinically relevant in neurological disorders such as spastic cerebral palsy to monitor disease progression and evaluate the effect of treatment. This study presents a methodology for extracting these parameters along with a clinical reliability analysis for the data acquisition and processing. Methods: The medial gastrocnemius muscles and Achilles tendon of 10 typically developing children and 10 children with spastic cerebral palsy were assessed. An open-source in-house software library developed in Python (Py3DFreeHandUS) was used to reconstruct, into one 3D data set, the data simultaneously acquired from an US machine and a motion tracking system. US images were manually segmented and linearly interpolated by means of a new simplified approach which involved sequentially decreasing the total number of images used for muscle border segmentation from 100% to 5%. Acquisition and processing reliability was defined based on repeated measures from different data processers and from different data acquirers, respectively. Results: When only 10% of the US images were outlined, there was an average underestimation of muscle volume of 1.1% and 1.6% with respect the computation of all the available images, for the typically developing and spastic cerebral palsy groups, respectively. For both groups, the reliability was higher for data processing than for data acquisition. High inter-class correlation coefficient values were found for processing and acquisition reliability, with worst case values of 0.89 and 0.61, respectively. The standard error of measurement, expressed as a percentage of the average volumes, was smaller than 2.6 ml (4.8%) in all cases. Conclusions: The present analysis demonstrates the effectiveness of applying 3D freehand ultrasonography in a clinical setting for analysing healthy and pathological paediatric muscle.